Bodhee Prep-Online CAT Coaching | Online CAT Preparation | CAT Online Courses

Get 30% OFF on CAT Crash Course. Code: LASTLAP. Course starts from 18th Sept Enroll Now

CAT 2019 Quant Question with Solution 24

Consider a function $f$ satisfying $f(x+y)=f(x) f(y)$ where x, y are positive integers, and $f(1)=2$. If $f(a+1)+f(a+2)+\ldots+f(a+n)=16\left(2^{n}-1\right)$ then a is equal to

Show Answer

Correct Answer: 3


$\Rightarrow f(a)f(1)+f(a)f(2)+...+f(a)f(n)=16\left( {{2}^{n}}-1 \right)$

$\Rightarrow f(a)\left( f(1)+f(2)+...+f(n) \right)=16\left( {{2}^{n}}-1 \right)$

Take n=1,

$\Rightarrow f(a)f(1)=16\left( {{2}^{1}}-1 \right)=16$

$\Rightarrow f(a)\times 2=16\Rightarrow f(a)=8$


$\begin{align} & f(a)\left( f(1)+f(2)+...+f(n) \right)=16\left( {{2}^{n}}-1 \right) \\ & \Rightarrow f(1)+f(2)+...+f(n)=2\left( {{2}^{n}}-1 \right) \\ \end{align}$

If n=2, then $f(1)+f(2)=2\left( {{2}^{2}}-1 \right)=6$

$\Rightarrow f(2)=6-f(1)=6-2=4$

If n=3, then $f(1)+f(2)+f(3)=2\left( {{2}^{3}}-1 \right)=14$

$\Rightarrow f(3)=6-f(1)-f(2)=14-2-4=8=f(a)$

Hence a =3.

CAT Online Course
Also Check: 841+ CAT Quant Questions with Solutions

CAT 2019 Slot-1

CAT 2019 Slot-2

CAT online Courses

CAT 2023 Mock Test Series

  • 400+ Topic Tests
  • 45 Sectional tests
  • 20 Mock Tests (Video Solutions)
  • Only at INR 2499

20% Discount Code: GET20

FREE CAT Prep Whatsapp Group

CAT 2023 Online Course at affordable price